Comparison of Shearography to Scanning Laser Vibrometry as Methods for Local Stiffness Identification of Beams. (21st October 2013) - Zastavnik, F.; Pyl, L.; Gu, J.; Sol, H.; Kersemans, M.; Van Paepegem, W.
ABSTRACT Local stiffness of Euler–Bernoulli beams can be identified by dividing the bending moment of a deformed beam by the local curvature. Curvature and moment distributions can be derived from the modal shape of a beam vibrating at resonance. In this article, the modal shape of test beams is measured by both scanning laser vibrometry (SLV) and shearography. Shearography is an interferometric optical method that produces full‐field displacement gradients of the inspected surface. Curvature can be obtained by two steps of derivation of the modal amplitude (in the case of SLV) or one step of derivation of the modal shape slope (in the case of shearography). Three specially prepared aluminium beams with a known stiffness distribution are used for the validation of both techniques. The uncertainty of the identified stiffness distributions with both techniques is compared and related to their signal‐to‐noise ratios. A strength and weakness overview at the end of the article reveals that the shearography is the technique that shows the most advantages.